PERANAN KEPALA SEKOLAH UNTUK MENINGKATKAN KUALITAS GURU DI SMK IBNU KHALDUN BALIKPAPAN - KALIMANTAN TIMUR - jurnalpps pps; Indra Prasetyo; C. Sri Hartati; Yudi Yudi (Prodi Magister Manajemen Universitas Wijaya Putra, 2022)
This study aims to identify and explain the role of the principal to improve the quality of teachers at SMK Ibnu Khaldun Balikpapan. Qualitative methods are used to identify and explain these objectives. The results of the research show that the quality of teachers can improve the quality of schools and be able to prosper the teachers. The role of the principal of the Ibnu Khaldun Balikpapan Vocational School in improving teacher human resources can be seen from the increase in teacher work discipline, getting support from structural leaders, foundations, supervisors, committees and teachers. From improving teacher discipline, in the learning process teachers must be on time and teach first before learning hours begin.